Pemberdayaan Masyarakat Dalam Pengalaman Ibu Bersalin Terhadap Asuhan Kebidanan di Kelurahan Ladang Bambu Kecamatan Medan Tuntungan - Sopiah, Sopiah; Violent, Violent (Journal of Community Development, 2023)
Indonesia is ranked 101 out of 149 countries that still have low quality health services, this can also be seen from the maternal and infant mortality rate which is still quite high, 50% of the contributor to maternal mortality is during labor. The importance of improving the health status of mothers and babies is that the government provides health workers as trained birth attendants in this case both midwives and doctors. So that if the helper is trained, it can provide quality service in accordance with health service standards and patient needs. Midwifery care service standards are a reference for midwives to carry out their duties, functions and roles in accordance with their competence and authority. This study aims to analyze the quality of midwifery care for pregnant women at the Medan Tuntungan Sub-district Health Center. This community service uses a qualitative approach with an in-depth interview method (Indepth Interview), primary data obtained from interview guidelines to 10 informants of postpartum mothers and triangulated to midwives and persons in charge using interview guidelines and observation sheets. The results of this community service show that the Puskesmas of Medan Tuntungan Subdistrict is very concerned about patient safety, this can be seen from the provision of care that is quite effective and timely, the services provided are patient-centeredness, and always fair to all patients, so it can be concluded that the Puskesmas of Medan Tuntungan Subdistrict has provided quality care in accordance with the dimensions of health service quality.